Gambaran Hasil Pemeriksaan HBSAG pada Petugas Layanan Kebersihan yang Bekerja - Kawatu, Tozua Toar; Lalangpuling, Indra Elisabet; Salanti, Sefanya Taicia; Sumenge, Dionysius; Barung, Elisabeth Natalia (Poltekkes Kemenkes Padang, 2025)
Hepatitis B is a disease caused by the Hepatitis B virus (HBV) that attacks the liver and can cause acute to chronic disease that can be transmitted through blood and other body fluids such as semen and saliva. The purpose of this study was to describe the results of HBsAg examinations on hospital cleaning service officers who work at Prof. Dr. R.D. Kandou Manado Central General Hospital (RSUP). This research method is descriptive with a purposive sampling technique. This study has received approval from the health research ethics committee of the Manado Ministry of Health Polytechnic. The sample in this study amounted to 33 people who met the inclusion criteria, namely having worked for more than one year, no history of hepatitis before working and willing to participate in the study. The specimen used in this study was a serum sample obtained from the results of whole blood centrifugation. Then the serum sample was examined using the ELISA (Enzyme-Linked Immunosorbent Assay) method. Results: The results showed that of the 33 respondents who underwent HBsAg examination, 2 people showed examination values ​​above the cut-off value on the ELISA reader reading. This study concluded that 6.0% of samples were found to be positive for HBsAg, so it is necessary to increase vigilance for cleaning service officers in hospitals.